Nuclear p62/SQSTM1 facilitates ubiquitin-independent proteasomal degradation of BMAL1. - Chenliang Zhang; Quanyou Wu; Huan Zhang; Ruichen Liu; Liping Li (PLoS Genetics)
Brain and muscle arnt-like protein 1(BMAL1) is a critical regulator of circadian rhythm. Although transcriptional regulation of BMAL1 has been extensively studied, the mechanisms governing the stability of BMAL1 at the protein level remain unclear. p62/SQSTM1 is a crucial factor in proteostasis regulation and is involved in both autophagy and the ubiquitin-proteasome system. We demonstrated that p62 promotes proteasomal degradation of BMAL1 within the nucleus, independent of ubiquitination. Additional molecular analyses indicated that p62 functions as a receptor for the 20S proteasome, facilitating the recruitment of BMAL1 to the 20S proteasome for degradation. This mechanism is independent of recently identified p62-driven nuclear biomolecular condensates. We also revealed that remodeling the nuclear accumulation of p62 may represent a potential strategy for targeting BMAL1 to suppress tumor cell growth. In conclusion, our findings revealed a novel mechanism by which nuclear p62 regulates BMAL1 proteostasis.